2009
DOI: 10.1579/0044-7447-38.8.432
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Ozone Concentration and Its Impact on Forest Vegetation in Lithuania

Abstract: Continuous ozone concentration measurements at rural sites in Lithuania have been performed since 1982. Long-term ozone data show an increasing trend 0.4 ppb y(-1) in annual mean concentrations during the period 1982-2008, although ozone peak values show an insignificant tendency to decrease. Several studies were performed to evaluate the ozone effect on the main plant species of Lithuanian forests. A strong positive correlation was found between values for the accumulated doses over a threshold of 40 ppb inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The monitored stands were located no further than 300 km from this EMEP station, which was the source of the longest data set on concentrations of acidifying compounds in this part of Europe, as well as their wet deposition and surface ozone. Preila EMEP station is under operation since 1981 (Girgzdiene et al 2009, Sopauskiene & Jasineviciene 2006. In this study, we used longer data sets from one station rather than shorter sets (data since 1994) from stations representing the considered regions.…”
Section: Methodsmentioning
confidence: 99%
“…The monitored stands were located no further than 300 km from this EMEP station, which was the source of the longest data set on concentrations of acidifying compounds in this part of Europe, as well as their wet deposition and surface ozone. Preila EMEP station is under operation since 1981 (Girgzdiene et al 2009, Sopauskiene & Jasineviciene 2006. In this study, we used longer data sets from one station rather than shorter sets (data since 1994) from stations representing the considered regions.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies provided statistical evidence that O 3 has a negative impact on crown defoliation, both in Southern Europe (Díaz-de-Quijano et al, 2009;Sicard and Dalstein-Richier, 2015) and in countries where the AOT40 values for forests are usually lower than in European southern countries, e.g. Lithuania (Augustaitis and Bytnerowicz, 2008;Girgždienė et al, 2009;Augustaitis et al, 2010;Araminiene et al, 2019) or Romania (De Marco et al, 2017). Ozone can also affect forest growth (McLaughlin et al, 2007;Matyssek et al, 2010;Braun et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The literature results regarding the ozone sensitivity of natural vegetation in northern Europe are contradictive. Subramanian et al (2014) reported a higher, modeled reduction of net primary production in conifers (4.3 − 15.5 %) than birch (1.4−4.3 %) under elevated ozone in Sweden, while Girgždienė et al (2009) observed more visible damage on deciduous trees than on Norway spruce in Lithuania. But visible damage and biomass reduction may not occur at the same rate and hence may not be interchangeable.…”
Section: Discussionmentioning
confidence: 98%
“…Results from open-top chamber (OTC) experiments on downy birch (Betula pubescens) and mountain birch (Betula pubescens toruosa), native to subarctic regions, indicated reductions in both biomass, in root:shoot ratio, and visible leaf damage under elevated ozone treatment ( [O 3 ] = 36 − 54 ppb) (Manninen et al, 2009). Though, Scots pine (Pinus sylvestris) is considered to be more ozone tolerant due to an absence of visible injuries (Girgždienė et al, 2009), Manninen et al (2009) found chlorophyll:carotenoid ratio and polyamines reductions under elevated ozone concentrations indicating susceptibility to ozone also in these species.…”
mentioning
confidence: 99%